PROGRAM REMEDIAL SEBAGAI UPAYA UNTUK MENCAPAI KETUNTASAN BELAJAR SISWA KELAS XI IPS I PADA MATA PELAJARAN AKUNTANSI - Syafi&rsquo (Pendidikan Ekonomi, 2010)
The current research is to investigate the implementation of the remedial program for the students who had not achieved the minimum learning mastery. The study is a classroom action research consisting of three cycles. The results of the study reveal that the teachers skill in managing the classroom and remedial program was good. The remedial program could enhance the students activities in learning process. The students learning mastery also increased in the three cycles; 91,42 %,,  91,89 %,, and 94,59% respectively. The use of remedial program was also considered positive by the students.